The Moderating Role of Place Attachment in The Influence of Destination Image on Revisit Intention at Lawang Tourist Destination in Agam District - Febrian Ananda; Youmil Abrian (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated because the tourist destination Lawang Agam Regency has a very high tourism potential due to natural factors that are very supportive for tourism. The purpose of this study is to analyze destination image, place attachment, and revisit intention in Lawang tourist destinations in Agam Regency. This study uses a type of causal associative research or cause-and-effect relationship because it uses quantitative methods. Data is obtained by dividing the survey results to research respondents. The destination image variable gets an average value of 4.19 with good criteria, a sample mean value of 0.848, a t-statistic value of 15.639 greater than 1.96 and a p-value of 0.000 less than 0.05. The place attachment variable obtained an average value of 3.81 with good criteria, a sample mean value of 0.196, a t-statistic value of 2.696 greater than 1.96 and a p-value of 0.007 smaller than 0.05. The average revisit intention variable was 4.13 with good criteria, Therefore, H1, H2, and H3 were accepted because of the positive and significant effects of destination image with revisit intention, place attachment with revisit intention, and place attachment variables moderating the relationship between destination image and revisit intention.